The impact of party pluralism on social and political stability in the Kurdistan Region of Iraq/ : A field study in political sociology - Rozhgar Hamadamin Ali; Tahir Hasoo Zebari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research discusses the impact of party pluralism on political and social stability in the Kurdistan Region. The research community consists of citizens of the Kurdistan Region who hold a bachelor’s degree or hold higher degrees. The sample consisted of a hierarchical sample, which consisted of (384) individuals as a sample for the research, by using the social survey approach. The research objectives also focused on identifying the level of pluralism and knowing the impact of demographic variables on the main variables of the research, which consist of (pluralism, political stability, and social stability). Besides, the research aims to identify the extent of the impact of partisan pluralism on the political and social stability of the members of the research sample. As for the most important results of the research, the research sample confirmed that it does not rely on the positivity of partisan pluralism. They also believe that partisan pluralism in the Kurdistan Region negatively affects social stability, but it has an effect. Positive on political stability.